Albert Sidney Burleson papers - Burleson, Albert Sidney, 1863-1937.
Correspondence, memoranda, articles, scrapbooks, printed matter, and other papers relating chiefly to Burleson's service as an aide to President Woodrow Wilson, U.S. postmaster general in Wilson's administration, and U.S. representative from Texas. Subjects include the federal takeover of telegraph, telephone, and cable facilities during World War I; wartime censorship; the Treaty of Versailles, 1919; political campaigns from 1894 to 1936; postal rates, parcel post facilities, and air mail service; and agricultural interests of Texas. Includes correspondence and memoranda (1912-1920) of Woodrow Wilson relating, in part, to postmasterships and to his illness in 1919. Burleson's correspondents include Newton Diehl Baker, Ray Stannard Baker, Henry Breckinridge, William Jennings Bryan, Newcomb Carlton, George Creel, Josephus Daniels, Thomas Watt Gregory, Herbert Hoover, Edward Mandell House, Cordell Hull, William V. Judson, Robert Lansing, W.G. McAdoo, Franklin D. Roosevelt, Theodore Roosevelt, Daniel C. Roper, and Theodore Newton Vail.
U.S. representative from Texas, postmaster general in Woodrow Wilson's cabinet, and Democratic Party leader.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Baker, Ray Stannard, -- 1870-1946 -- Correspondence; Breckinridge, Henry, -- 1886-1960 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Carlton, Newcomb, -- 1869-1953 -- Correspondence; Creel, George, -- 1876-1953 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Gregory, Thomas Watt, -- 1861-1933 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Judson, William V. -- 1865-1923 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Roper, Daniel C. -- 1867-1943 -- Correspondence; Vail, Theodore Newton, -- 1845-1920 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924 -- Correspondence; United States. -- Post Office Department; Democratic Party (U.S.); Treaty of Versailles -- (1919); Agriculture -- Texas; Air mail service -- United States; Parcel post -- United States; Postal rates -- United States; Postal service -- United States; Presidents -- United States -- Election; Telegraph -- Law and legislation -- United States; Telephone -- Law and legislation -- United States; World War, 1914-1918 -- Censorship -- United States; World War, 1914-1918 -- Communications; World War, 1914-1918 -- Peace; Texas -- Politics and government; United States -- Politics and government -- 1901-1953.; Cabinet officers; Representatives, U.S. Congress -- Texas